Characterization of Acoustic Infrasound Signals at Volcán de Fuego, Guatemala: A Baseline for Volcano Monitoring - Diaz-Moreno, A.; Roca, A.; Lamur, A.; Munkli, B. H.; Ilanko, T.; Pering, T. D.; Pineda, A.; De Angelis, S. (Frontiers in Earth Science, 2020)
On June 3, 2018, Volcan de Fuego, Guatemala, produced a violent eruption with very little warning; the paroxysmal phase of this event generated pyroclastic density currents that impacted nearby settlements resulting in 169 fatalities, 256 missing, and nearly 13,000 permanently displaced from their homes. Since then, Volcan de Fuego has been instrumented with an extensive network of seismic and infrasound sensors. Infrasound is a new monitoring tool in Guatemala; the first key step towards its effective use in volcano monitoring at Volcan de Fuego is establishing a baseline for the interpretation of the recorded signals. Here, we present the first comprehensive characterization of infrasound signals at Volcan de Fuego spanning the broad spectrum of activity observed at the volcano. We use data collected during temporary deployments between 2009 and 2018, and more recently from the permanent infrasound network. We identify distinctive, short-duration, acoustic transients related to ash-rich and gas-rich explosions, at times associated with the generation of shock-waves; the rich infrasound record at Volcan de Fuego also includes examples of sustained tremor, from broadband to harmonic, and episodes of so-called chugging. Finally, building on past work, we discuss a conceptual model of the shallow conduit system to assist with the interpretation of the processes responsible for the generation of infrasound at Volcan de Fuego. This study provides a reference for the interpretation of acoustic signals at Volcan de Fuego and a baseline for real-time monitoring of its eruptive activity using infrasound.